Changes in Management Systems of Jeopardized Organizations - Skalik, Jan (Zmiany w systemie zarządzania zagrożonymi organizacjami, 2010)
One of the reasons for destabilization of equilibrium in economic organizations is the neglect of internal dangers resulting from the inefficiency of company management systems. Basing on the presentation of a management system concept, we postulate changes in the architecture of such systems that may effectively eliminate or limit the impact of internal dangers, resulting in an increased positive potential of the organization.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 69-75
Keywords: organizational threats; organizational equilibrium; organizational change